IMPACT OF CHRONIC NOISE ON HIPPOCAMPAL MORPHOLOGY AND ITS FUNCTIONS IN WISTAR ALBINO RATS - ARJUNAN, ARCHANA; RAJAN, RAVINDRAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study aims to investigate the effect of chronic noise stress on hippocampal morphology and its functions in male Wistar albino rats. Methods: Adult albino rats were randomly divided into two groups. Each group contained six animals. Rats exposed to chronic noise stress (100 dB/4 h–30 days) were compared with control animal and assessed for behavior using hole-board test, marble burying test, and morphology of hippocampus by histology. Results: The rats exposed to chronic noise stress showed significance (P < 0.05) of behavioral alterations such as increased fear and anxiety, obsessive-compulsive behavior, enlarged lateral ventricle, and reduced hippocampal volume. Conclusion: The results reported that chronic noise stress affects neurobehavioral due to reduced hippocampal volume.